New model of superior semicircular canal dehiscence with reversible diagnostic findings characteristic of patients with the disorder - Wackym, P. Ashley; Balaban, Carey D.; Van Osch, Olivia J.; Morris, Brian T.; Tamakloe, Mark-Avery; Salvatore, Victoria L.; Duwadi, Sudan; Gay, Jennifer D.; Mowery, Todd M. (Frontiers in Neurology, 2023)
Background Third window syndrome is a vestibular-cochlear disorder in humans in which a third mobile window of the otic capsule creates changes to the flow of sound pressure energy through the perilymph/endolymph. The nature and location of this third mobile window can occur at many different sites (or multiple sites); however, the most common third mobile window is superior semicircular canal dehiscence (SSCD). There are two essential objective diagnostic characteristics needed to validate a model of SSCD: the creation of a pseudoconductive hearing loss and cVEMP increased amplitude and decreased threshold. Methods Adult Mongolian gerbils (n = 36) received surgical fenestration of the superior semicircular canal of the left inner ear. ABR and c+VEMP testing were carried out prior to surgery and over acute (small 1 mm SSCD, 1–10 days) or prolonged (large 2 mm SSCD, 28 days) recovery. Because recovery of function occurred quickly, condenser brightfield stereomicroscopic examination of the dehiscence site was carried out for the small SSCD animals post-hoc and compared to both ABRs and c+VEMPs. Micro-CT analysis was also completed with representative samples of control, day 3 and 10 post-SSCD animals. Results The SSCD created a significant worsening of hearing thresholds of the left ear; especially in the lower frequency domain (1–4 kHz). Left (EXP)/right (CTL) ear comparisons via ABR show significant worsening thresholds at the same frequency representations, which is a proxy for the human pseudoconductive hearing loss seen in SSCD. For the c+VEMP measurements, increased amplitude of the sound-induced response (N1 2.5 ms and P1 3.2 ms) was observed in animals that received larger fenestrations. As the bone regrew, the c+VEMP and ABR responses returned toward preoperative values. For small SSCD animals, micro-CT data show that progressive osteoneogenesis results in resurfacing of the SSCD without bony obliteration. Conclusion The large (2 mm) SSCD used in our gerbil model results in similar electrophysiologic findings observed in patients with SSCD. The changes observed also reverse and return to baseline as the SSCD heals by bone resurfacing (with the lumen intact). Hence, this model does not require a second surgical procedure to plug the SSCD.